Brain Network Segregation and Glucose Energy Utilization: Relevance for Age-Related Differences in Cognitive Function. (22nd June 2020) - Manza, Peter; Wiers, Corinde E; Shokri-Kojori, Ehsan; Kroll, Danielle; Feldman, Dana; Schwandt, Melanie; Wang, Gene-Jack; Tomasi, Dardo; Volkow, Nora D
Abstract: The human brain is organized into segregated networks with strong within-network connections and relatively weaker between-network connections. This "small-world" organization may be essential for maintaining an energetically efficient system, crucial to the brain which consumes 20% of the body's energy. Brain network segregation and glucose energy utilization both change throughout the lifespan. However, it remains unclear whether these processes interact to contribute to differences in cognitive performance with age. To address this, we examined fluorodeoxyglucose-positron emission tomography and resting-state functional magnetic resonance imaging from 88 participants aged 18–73 years old. Consistent with prior work, brain network segregation showed a negative association with age across both sensorimotor and association networks. However, relative glucose metabolism demonstrated an interaction with age, showing a negative slope in association networks but a positive slope in sensorimotor networks. Overall, brain networks with lower segregation showed significantly steeper age-related differences in glucose metabolism, compared with highly segregated networks. Sensorimotor network segregation mediated the association between age and poorer spatial cognition performance, and sensorimotor network metabolism mediated the association between age and slower response time. These data provide evidence that sensorimotor segregation and glucose metabolism underlie some age-related changes in cognition. Interventions that stimulate somatosensory networks could be important for treatment of age-related cognitive decline.